Antimicrobial activity of the biogenically synthesized core-shell Cu@Pt nanoparticles - Renata Dobrucka; Jolanta Dlugaszewska (Elsevier, 2018)
The interest in the biological synthesis of mono metal nanoparticles has been visible for years. As more attention is also given to the biological methods of synthesizing bimetallic nanoparticles, this work used the Agrimoniae herba extract in order to obtain bimetallic core-shell Cu@Pt nanoparticles. The formed core-shell Cu@Pt nanoparticles were characterized by Ultraviolet-Visible (UV-vis), Fourier Transform-Infrared (FT-IR), Scanning electron microscopy (SEM), Transmission Electron Microscopy (TEM) and Atomic Force Microscopy (AFM) measurements. The obtained core-shell Cu@Pt nanoparticles were analysed in terms of their antibacterial activity. It was discovered that the synthesized nanoparticles exhibited maximum activity against gram-negative bacteria E. coli ATCC 25922, S. aureus ATCC 25923, and P. aeruginosa NCTC 6749. The core-shell Cu@Pt nanoparticles also exhibited activity against the yeast C. albicans ATCC 10231 and dermatophytes T. mentagrophytes ATCC 9533. Keywords: Cu@Pt nanoparticles, Biogenic synthesis, Antimicrobial activity